2016
DOI: 10.1017/aae.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

The Rainfall Index Annual Forage Pilot Program as a Risk Management Tool for Cool-Season Forage

Abstract: Abstract.The recently implemented Rainfall Index Annual Forage pilot program aims to provide risk coverage for annual forage producers in select states through the use of area rainfall indices as a proxy for yield. This article utilizes unique data from a long-term study of annual ryegrass production with rainfall recorded at the site to determine whether the use of rainfall indices provides adequate coverage for annual forage growers. The rainfall index is highly correlated with actual rainfall. However, it d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Our conceptual model modifies Maples, Brorsen, and Biermacher (2016), by allowing monthly insurance interval selection in a perennial forage system. We assume producers are risk averse, expected-utility maximizers and can choose to purchase insurance.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Our conceptual model modifies Maples, Brorsen, and Biermacher (2016), by allowing monthly insurance interval selection in a perennial forage system. We assume producers are risk averse, expected-utility maximizers and can choose to purchase insurance.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…It is an expected result as pasture cultivation is quite different from the development of arable crops, where normal distributions in the NDVI values are more common. This high heterogeneity in time and space of NDVI estimated on pasture has been pointed out in several works (Martin-Sotoca et al, 2018). At the same time, the more different the observed NDVI frequency is from a normal distribution, the less representative the average is, and so the median becomes a more representative value.…”
Section: χ 2 Testmentioning
confidence: 86%
“…Two examples of SIBIs are presented in two different countries: the USA and Spain. In particular, in the USA there are several insurance programs for pasture, rangeland and foraging, which use various indexing systems (rainfall and vegetation indices) and are promoted by the Unites States Department of Agriculture (USDA) (Maples et al, 2016;USDA, 2018). NDVI is the index chosen in the vegetation index program, and it is obtained from the AVHRR (Advanced Very High Resolution Radiometer) sensor aboard NOAA satellites.…”
Section: Introductionmentioning
confidence: 99%
“…The RIAFP utilizes rainfall indices from weather data collected by NOAA. Maples et al (2016) found that RIAFP was successful in transferring income to participating forage producers, but they did not find a correlation between rainfall and forage yield, so RIAFP was risk increasing rather than risk reducing. Is the premise that forage yield is correlated with monthly precipitation a false assumption?…”
Section: Introductionmentioning
confidence: 94%
“…Is the premise that forage yield is correlated with monthly precipitation a false assumption? Before reaching such a conclusion, however, it is important to note that the study conducted by Maples et al (2016) only studied one site on sandy soil with changing species over time. Inclusion of multiple sites with different soil types and consistent species could provide information on the robustness and generality of their findings.…”
Section: Introductionmentioning
confidence: 99%